Are professional basketball players reference-dependent?. Issue 36 (2nd August 2018) - Lusher, Lester; He, Chuan; Fick, Stephen
ABSTRACT: Models with reference-dependent preferences suggest that agents exert considerable effort to avoid falling below a reference point and 'losing'. We provide visual and statistical evidence that player performances in the National Basketball Association (NBA) bunch at salient, normatively extraneous round numbers. Using data on nearly three million shot attempts with precise (x, y ) coordinates, we find that players improve free throw accuracy and attempt shots closer to the hoop when shooting for a round number. The results are strongest for players on home teams, suggesting that the reference-dependent enters preferences through an external, social evaluation channel.